2019
DOI: 10.1007/s00408-018-00192-2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Cerebellum in Control of Swallow: Evidence of Inspiratory Activity During Swallow

Abstract: Anatomical connections are reported between the cerebellum and brainstem nuclei involved in swallow such as the nucleus tractus solitarius (NTS), nucleus ambiguus, and Kölliker-fuse nuclei. Despite these connections, a functional role of the cerebellum during swallow has not been elucidated. Therefore, we examined the effects of cerebellectomy on swallow muscle recruitment and swallow-breathing coordination in anesthetized freely breathing cats. EMG recordings were collected from upper airway, pharyngeal, lary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
1
11
1
1
Order By: Relevance
“…Afferent projections from the larynx are represented in the cerebellum [ 16 ], and perhaps this feedback regulates motor output to maintain a set point for laryngeal stiffness during cough. Interestingly, we observed the opposite effect of cerebellectomy on thyroarytenoid activity during swallow reported in Reed and colleagues [ 51 ]. These data in combination with what is previously understood about breathing demonstrate a clear need for research on all pattern generators important for airway protection, as the effects on a single behavior are not translated to others.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Afferent projections from the larynx are represented in the cerebellum [ 16 ], and perhaps this feedback regulates motor output to maintain a set point for laryngeal stiffness during cough. Interestingly, we observed the opposite effect of cerebellectomy on thyroarytenoid activity during swallow reported in Reed and colleagues [ 51 ]. These data in combination with what is previously understood about breathing demonstrate a clear need for research on all pattern generators important for airway protection, as the effects on a single behavior are not translated to others.…”
Section: Discussioncontrasting
confidence: 74%
“…Williams et al [ 50 ] similarly reported a prolonged T TOT and T E (in addition to a slightly prolonged T I ) and a reduced respiratory frequency post-cerebellectomy in vagal intact animals. However, several other publications reported no change in eupneic breathing values in vagally intact animals [ 40 , 51 53 ]. At least one study did report increased respiratory frequency, but this sample included some vagotomized animals [ 49 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Clinically, it has been assumed that swallow duration positively correlates with force production, as defined by swallow phase relationships in videofluoroscopy exams [13]. We have now established that swallow-related EMG amplitude and duration are not correlated in cats [13,46,73], humans [74,75], or rats (present study). The inability to assess this using visual metrics (videofluoroscopy and endoscopy) supports the need for development of "strength" related clinical metrics in order to better investigate this property of swallow pattern generation.…”
Section: Emg Amplitude and Duration Are Not Correlatedmentioning
confidence: 48%
“…Furthermore, adults with CP have a greater risk of respiratory disease than adults in the general population [17,18]. The DIAm plays a critical role in reducing susceptibility to respiratory infections in two ways: 1) during the pharyngeal phase of swallowing, the DIAm generates a large negative intrathoracic pressure necessary to propel a food bolus through the pharynx and into the esophagus, with failure resulting in aspiration; and 2) coughing and sneezing, where the DIAm contributes to increased intraabdominal pressure necessary to expel aspirates and phlegm from the airway [11,[19][20][21]. Therefore, we propose that we should educate families of children with CP that their child may also have an impaired cough, which can increase their child's susceptibility to respiratory complications.…”
mentioning
confidence: 99%